2017
DOI: 10.1038/nsmb.3350
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the secretin translocation channel in the type II secretion system

Abstract: The secretin GspD of the type II secretion system (T2SS) forms a channel across the outer membrane in Gram-negative bacteria to transport substrates from the periplasm to the extracellular milieu. The lack of an atomic-resolution structure of the GspD channel hinders the investigation of substrate translocation mechanism of T2SS. Here we report cryo-EM structures of two GspD channels (∼1 MDa), from Escherichia coli K12 and Vibrio cholerae, at ∼3 Å resolution. The structures reveal a pentadecameric channel arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
195
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(204 citation statements)
references
References 51 publications
8
195
1
Order By: Relevance
“…Based on sequence analysis, the authors previously proposed that the EPEC secretin belongs to the Vibrio-type subfamily (14). In agreement with sequence similarities, a similar structural architecture can be seen between the two Vibrio-type secretins, i.e., the EPEC structure from the work of Hay et al (6) and the Vibrio structure from the work of Yan et al (15), with loops extending from the extracellular side to form the typical cap gate (Fig. 1).…”
supporting
confidence: 66%
See 2 more Smart Citations
“…Based on sequence analysis, the authors previously proposed that the EPEC secretin belongs to the Vibrio-type subfamily (14). In agreement with sequence similarities, a similar structural architecture can be seen between the two Vibrio-type secretins, i.e., the EPEC structure from the work of Hay et al (6) and the Vibrio structure from the work of Yan et al (15), with loops extending from the extracellular side to form the typical cap gate (Fig. 1).…”
supporting
confidence: 66%
“…The cap gate of the Vibrio-type channel has a cone-like structure formed by 15 pairs of antiparallel ␤12-␤13 strands. The linker loops between outer ␤-barrel and cap gate (␤12 and ␤13 strands) are relatively loose, which suggests that the cap gate of the Vibrio type is probably independent of other structural parts, therefore constituting a signature distinguishing two different classes of secretins (15). The internal diameters of the cap and central gates of the secretins are not compatible with the diameters of the secreted substrates and therefore suggest that purified full-length secretins are in a "closed state" and must undergo conformational changes during the secretion process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…S2). Analysis of other T2SS secretin structures (26) revealed that these inter-and intrasubunit salt bridges that tie the subunits together are conserved, thereby providing an explanation for the welldocumented thermal and chemical quaternary stability of secretin complexes (9).…”
mentioning
confidence: 97%
“…Recently, Yan et al solved the structure of the secretin from V. cholerae (26), providing a basis to assess the similarities of the two secretins.…”
mentioning
confidence: 99%